Determination of iohexol by capillary blood microsampling and UHPLC-MS/MS - Valentin Ion; Caroline Legoff; Etienne Cavalier; Pierre Delanaye; Anne-Catherine Servais; Daniela-Lucia Muntean; Marianne Fillet (Elsevier, 2019)
One of the most important tools used to evaluate kidney function in the context of chronic kidney disease or other renal function related pathologies is the exploration of glomerular filtration rate (GFR). Iohexol is up to this moment a good candidate molecule for the GFR assessment since it exhibits minimum protein binding rates and minimum extra-renal clearance, being neither secreted nor reabsorbed at the tubular level. This study proposes and evaluates a new LC-MS/MS method for the iohexol determination from capillary blood, prelevated using volumetric absorbative microsampling (VAMS) systems. As an alternative to VAMS, a brand new HemaPEN® device for micro-prelevation was also tested. A new high throughput sample preparation protocol adapted for iohexol quantification from whole blood VAMS samples was developed. The medium term stability study of iohexol in dried whole blood VAMS samples that was conducted showed a good stability of this molecule for up to 12 days. By collecting only 10 μL of blood, iohexol can be analyzed from dried whole blood VAMS samples for concentration ranges between 1 and 250 μg/mL. Due to the analyte stability in VAMS for up to 12 days, this approach might be successfully applied for GFR assessment for clinical cases allowing minimum invasiveness and even delayed analysis. Keywords: Microsampling, Iohexol, VAMS, LC-MS/MS, HemaPEN